Opportunities And Challenges of Indonesian Sharia Banking Digital Services for Hajj-Umrah in Saudi Arabia - Sabbahatun, Sri; Said, Muhammad; Nafis, Muhammad Cholil; Rusydiana, Aam (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Indonesia's growing Hajj and Umrah pilgrim population, along with a significant number of Indonesian expatriates in Saudi Arabia, has increased the demand for accessible and efficient Sharia-compliant financial services. The purpose of this paper is to analyze strengths, weaknesses, opportunities and threats (SWOT) Indonesian sharia banking digital services for Indonesian citizens in Saudi Arabia (Hajj and Umrah pilgrims as well as Indonesian citizens living in Saudi Arabia) and finally prioritizing strategies according to expert assessments, including experts, practitioners, regulators and stakeholders. Since SWOT analysis is unable to rank the strategies developed, an analytical network process method is applied to prioritize them according to expert judgment. The results are compared with the results of the Analytic Network Process (ANP). The results of this research analysis found that the SWOT analysis found strengths, weaknesses, threats and opportunities in Indonesian sharia banking digital services for Indonesian citizens in Saudi Arabia. The criteria tested are digital sharia banking services, sharia banking regulations, budget, human resources, infrastructure. The results of the ANP analysis found that regarding the criteria for aspects of digital sharia banking services in Indonesia for Indonesian citizens in Saudi Arabia, the indicator that is the main priority is infrastructure. Then, in the sub-criteria for the digital service aspect of sharia banks, the main indicator is mobile banking, the sub-criteria for sharia banking regulations is the MoU on sharia banking in Indonesia and Saudi Arabia. Furthermore, the main indicators in the budget sub-criteria are costs required in Indonesia, the HR sub-criteria are IT HR in sharia banking in Saudi Arabia, and finally in the infrastructure sub-criteria is infrastructure in Indonesian sharia banking